Answer:
C) With the given general term, given sequence is -6, -4, -2, 0, 2,...
Step-by-step explanation:
Here, the first term f(1) = -6
The general term of the sequence :
f(n) = f(n-1) + 2
Now, we find the next five terms from the given general term:
For n = 2 : f(2) = f(2-1) + 2
= f(1) + 2 = -6 + 2 = -4
⇒ f(2) = -4
For n = 3 : f(3) = f(3-1) + 2
= f(2) + 2 = -4 + 2 = -2
⇒ f(3) = -2
For n = 4 : f(4) = f(4-1) + 2
= f(3) + 2 =-2 + 2 = 0
⇒ f(4) = 0
For n = 5 : f(5) = f(5-1) + 2
= f(4) + 2 =0 + 2 = 2
⇒ f(5) = 2
Hence with the given general term, given sequence is -6, -4, -2, 0, 2,...